The Impact of Transparency on Achieving Effective Procurement in the Syrian Telecommunication Sector - Alasfar, Wael (Technium Business and Management, 2022)
The purpose of this paper is to investigate the impact of transparency on achieving effective procurement in the Syrian Telecommunication Sector. In addition, it aims to assessing the level of awareness and understanding the concepts of transparency and effective procurement in the Syrian context. The research methodology involved the adoption of a survey as a research strategy and quantitative approach, utilized a self-administered questionnaire, to arrive at the major findings of the study. The type of research is a single cross-sectional design in which the collection of data from the respondents was carried out only once. Data was analyzed using the statistical package for social sciences (SPSS). The paper revealed that there is an impact of transparency on achieving effective procurement in the Syrian Telecommunication Sector. It also revealed that there is a high level of awareness among the respondents about the concepts of transparency and effective procurement. As far as the researcher is aware, this paper is the first to investigate the impact of transparency on achieving effective procurement in the Syrian telecommunication sector; thus its finding will be an original contribution to the field of transparency and effective procurement. In addition, as there has been a shortage of research in the field of transparency, generally in the Middle East countries, the researcher hopes that this paper will establish a foundation for further research in the region.